International Multiparty Mediation and Conflict Management Challenges of Cooperation and Coordination - Vukovic, Sinisa (Routledge Studies in Security and Conflict Management, 2016)
This volume aims to provide a detailed explanation of the effects of cooperation and coordination on international multiparty mediation in conflicts. Contemporary scholarship stresses that the crucial ingredients for a successful multiparty mediation are 'consistency in interests' and 'cooperation and coordination' between mediators. This book seeks to supplement that understanding by investigating how much the 'consistency of interests' and 'cooperation and coordination' affect the overall process, and what happens to the mediation process when mediating parties do not share the same idea and interest in finding a common solution. At the same time, it explores the obstacles in achieving coordination and coherence between various mediators in such an environment and how to surmount the problems that multiple mediators face when operating without a 'common script' in attempting to mediate a negotiated settlement. The study investigates three distinct mechanisms (both on the systemic and contextual level) that have the potential to deter defection from a (potential) member of the multiparty mediation coalition: geo-political shifts, changes in the conflict dynamics, and mediators' ability to bargain for a cooperative relationship. As the number of states and international actors that are involved in mediation increases, a careful assessment is necessary not only of their relative institutional strengths and weaknesses, but also of how to promote complementary efforts and how to synchronize the whole process when one actor is transferring the responsibilities for mediation to others. This book will be of much interest to students of mediation, conflict management, war and conflict studies, security studies and IR.